Chest wall fistula in a patient with pyothorax‐associated lymphoma. Issue 4 (25th February 2021) - Takahashi, Saeko; Omura, Kenshiro; Nakamura, Morio
Key message: Fistula formation is an uncommon but serious therapeutic complication of pyothorax‐associated lymphoma (PAL) because it decreases the quality of life in patients. Furthermore, a collapsed lung may predispose to pneumonia. In PAL, the lesions might invade the skin and optimal irradiation dose, region, and timing should be carefully determined. Abstract : Fistula formation is an uncommon but serious therapeutic complication of pyothorax‐associated lymphoma (PAL) because it decreases the quality of life in patients. Further, a collapsed lung may predispose to pneumonia. In PAL, the lesions might invade the skin and optimal irradiation dose, region, and timing should be carefully determined.